Analysis of Muallaf ‘Aisyiyah Da’wah Strategy - Casmini Casmini (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
Muallaf has psychological and social problems, so he needs adequate proselytizing. The assistance of Muallaf requires management in a systematic, planned, and carried out by gradually. This study aims to explore the analysis of Muallaf 'Aisyiyah's da'wah was carried out to see the precision and speed of service according to the characteristics of the problems facing Muslim convert and strength Strengthening given by 'Aisyiyah to optimize the guidance and counseling services to convert to Islam. The study subjects numbered 55 muballighat from 23 provinces which were excavated through a self-report written in the preachers' training of Aisyiyah, a companion to a Muslim muallaf with instruments prepared as worksheets in the training. The research results describe that SWOT analysis be one solution in formulating appropriate planning and prompt assistance following the problems faced by muallaf. Strengthening the preachers' competence in implementing the mentoring strategy planning is important in efforts to set goals and targets according to the needs of converts. Steps in building of Islamic faith and Islamic, psychological and spiritual strengthening, strengthening family resilience and economic empowerment and well-being executed based on a thorough analysis. Muallaf memiliki permasalahan ideologis, psikologis dan sosial, maka dirinya membutuhkan bantuan yang memadai. Proses memberikan bantuan kepada muallaf membutuhkan pengelolaan secara sistematis, terencana dan dilakukan dengan secara bertahap. Penelitian ini bertujuan menggali analisis dakwah muallaf ‘Aisyiyah yang dilakukan untuk melihat ketepatan dan kecepatan layanan sesuai karakteristik masalah yang dihadapi muallaf serta penguatan yang diberikan oleh ‘Aisyiyah dalam upaya optimalisasi layanan bimbingan dan konseling kepada muallaf. Subyek penelitian berjumlah 55 muballighat dari 23 provinsi yang digali melalui self-report yang dituliskan dalam pelatihan muballighat ‘Aisyiyah pendamping muallaf dengan instrumen yang disiapkan sebagai lembar kerja dalam pelatihan. Hasil penelitian mendeskripsikan bahwa analisis SWOT menjadi salah satu solusi dalam memformulasikan perencanaan pendampingan yang tepat dan cepat sesuai dengan permasalahan yang dihadapi oleh muallaf. Penguatan kompetensi muballighat dalam melaksanakan perencanaan strategi pendampingan menjadi penting dalam upaya menyusun tujuan dan target sesuai kebutuhan muallaf. Langkah-langkah dalam penguatan aqidah dan keislaman, penguatan psikologis dan spiritualitas, penguatan ketahanan keluarga dan pemberdayaan ekonomi dan kesejahteraan dijalankan berdasarkan pada analisis yang matang.